Sort by

- Relevance
- |Time

... / (EI) ==> M = y'' EI Looking at the

**LHS**of the Beam P/2 ======= P ======= P/2 | ------ x...1 Answers · Science & Mathematics · 16/01/2014

...u(x) to get u(x)y' + P(x)u(x)y = u(x)g(x) Notice that the

**LHS**becomes an exact differential, d(u(x)y). Given: y dx - 4(x + y^6...1 Answers · Science & Mathematics · 18/02/2014

... should check this back to see that it satisfies the differential equation (

**LHS**) but no time I'm afraid! We now have to find any particular solution...2 Answers · Science & Mathematics · 19/03/2013

..., so the only vertical forces in the cut members in the

**LHS**of the truss are in CG. Then the vertical load in CG...1 Answers · Science & Mathematics · 31/01/2012

y1'(t) = 0 y2'(t) = 3(t-t0)^2 Then, for y1:

**LHS**: y'(t) = 0 RHS: 3y^(2/3) = 3(0)^(2/3) = 0 ✓ And for y2:**LHS**: y'(t) = 3(t-0)^2 = 3t^2 RHS: 3y^(2/3) = 3[(t-0)^3]^(2/3) = 3t^2 ✓1 Answers · Science & Mathematics · 30/09/2009

...91 is a transformation of Eqn 2-88, using 2-89 to replace the

**LHS**and using 2.90 to replace the RHS of 2-88. Eqn 2-92 ...1 Answers · Science & Mathematics · 26/05/2013

...of the RHS is obviously ln(x) + C. Integral of the

**LHS**looks tough, trying Wolfram Integrator if you'...1 Answers · Science & Mathematics · 02/07/2013

1. Simplify the given equation. 2. Move all the unknowns(usually the subject) on your

**LHS**and the rest of the known values on the RHS 3. Equate them to get the answer.1 Answers · Science & Mathematics · 17/03/2014

...on the left hand side should be equal to the values on the right hand side.

**LHS**=((A+.(B.C) A.C+B))’ RHS=A...1 Answers · Science & Mathematics · 22/09/2012

...n-1 Subtract to get n(1)'s = (10^n+1-10^n-9)/81 If n=5,

**LHS**= 11111. RHS = (10^6-10^5-9)/81, which is indeed true. 10^6-10^5 = 9...1 Answers · Science & Mathematics · 18/06/2011